2016
DOI: 10.21767/2472-0151.100019
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Evaluation of Various Solvent Extracts of the Leaves, Fruits and Shoots of Ferula Jaeschkeana Vatke

Abstract: The genus Ferula possess strong aromatic smell due to the presence of essential oil or oleoresin and is well-known in folk medicine for the treatment of various disorders. The present study aimed to investigate the presence of phytochemicals in various solvent extracts of leaves, fruits and shoots of Ferula jaeschkeana Vatke. This study investigates the effects of ethanol, methanol, chloroform, petroleum ether and aqueous extracts of leaves, fruits and shoots. Phytochemical screening revealed the presence of v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 8 publications
1
5
0
Order By: Relevance
“…Saponin derived its name from the formation of stable soapy foam in water solutions, hence, it is typically present in aqueous extracts thereby justifying its presence in this study. This is in line with the result reported by Yaqoob et al, [19] for Ferula Jaeschkeana Vatke leaves where saponin was present in the aqueous extract. Saponin apart from its foaming abilities, also protects against microbial attack in plants; it is helpful in treating yeast and fungal infections [20].…”
Section: Discussionsupporting
confidence: 93%
“…Saponin derived its name from the formation of stable soapy foam in water solutions, hence, it is typically present in aqueous extracts thereby justifying its presence in this study. This is in line with the result reported by Yaqoob et al, [19] for Ferula Jaeschkeana Vatke leaves where saponin was present in the aqueous extract. Saponin apart from its foaming abilities, also protects against microbial attack in plants; it is helpful in treating yeast and fungal infections [20].…”
Section: Discussionsupporting
confidence: 93%
“…These findings are in agreement with those reported by Sultana et al, [14] who reported good extract yields from the bark of different plants when extracting with 80% ethanol. Moreover, Yaqoob et al, [15] reported the phytochemical screening of leaves, fruits, and shoots of Ferula jaeschkeana Vatke that revealed presence of more number of phytochemicals in shoots than leaves and fruits, especially with ethanolic extracts. We suspect that the bark contains the highest extractable phytochemicals followed by leaves, and then roots [14,15] .…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, Yaqoob et al, [15] reported the phytochemical screening of leaves, fruits, and shoots of Ferula jaeschkeana Vatke that revealed presence of more number of phytochemicals in shoots than leaves and fruits, especially with ethanolic extracts. We suspect that the bark contains the highest extractable phytochemicals followed by leaves, and then roots [14,15] . This library represents the potential phytochemicals in herbal prescriptions dispensed by traditional healers in Lesotho and serves for primary access for screening against various target pathogenic microbes, as well as for isolation of active compounds toward new antibiotic drug discovery.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have revealed that soil attributes are of the main parameters in distribution of plant societies, particularly in arid land (Goodal and Perry, 1979) and correlation of some soil chemical characters as well as soil humidity with vegetation cover have been documented in different studies (Dyakov, 2014;Sheikh et al, 2014;Gemedo et al, 2014 Yaqoob and Nawchoo, 2016). It has large presence in Asia, particularly in Turkey, Iran and Turkmenistan compared to other genera in the family (Pimenov and Leonov, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…It has large presence in Asia, particularly in Turkey, Iran and Turkmenistan compared to other genera in the family (Pimenov and Leonov, 1993). Thirty-two species of Ferula have been reported from Iran, where some of its species are known as Endemic (Mozaffarian, 1983;2007;Yaqoob and Nawchoo, 2016). The popular Persian name of the most of Ferula species is "Koma" and F. ovina (Boiss.)…”
Section: Introductionmentioning
confidence: 99%